Low-temperature-poling awakened high dielectric breakdown strength and outstanding improvement of discharge energy density of (Pb, La)(Zr, Sn, Ti)O3 relaxor thin film. (November 2020) - Peng, Biaolin; Tang, Silin; Lu, Li; Zhang, Qi; Huang, Haitao; Bai, Gang; Miao, Lei; Zou, Bingsuo; Liu, Laijun; Sun, Wenhong; Wang, Zhong Lin
Abstract: Ferroelectric thin films possessing high dielectric breakdown strength ( DBS ) are attractive materials employed to satisfy the requirements of miniaturization and integration of electronic components, especially for dielectric capacitors with large discharge energy density ( W ). In this work, it is demonstrated for the first time that high DBS in ferroelectric thin film can be awakened by a low-temperature-poling method. Mn-doped Pb0.97 La0.02 (Zr0.905 Sn0.015 Ti0.08 )O3 (PLZST) relaxor thin films were prepared by using a sol-gel method, as when poled at near liquid nitrogen temperature, its DBS and W at room temperature are greatly enhanced (nearly doubled) from 1286 kV/cm to 2000 kV/cm, and from 16.6 J/cm 3 to 31.2 J/cm 3, respectively. The high ordering of defect dipoles during the low-temperature-poling process is responsible for the great enhancement of the awakened DBS and the outstanding improvement of the W . It concludes that the low-temperature-poling method can provide a new alternative strategy to strength the DBS and thus to improve the electrical performances of ferroelectric materials for the applications required strong electric fields in many fields, especially for dielectric energy storage, electrocaloric cooling, and energy harvesting, etc. Graphical abstract: Image 1 Highlights: A low-temperature-poling method to enhance DBS was explored for the first time. The high ordering of defect dipoles is responsible for the awakened DBS. The proposed method is applicable for many fields required strong electric field.